Complete heart block and itchy rash in a patient with COVID-19 - Mohammad Dehghani Firouzabadi; Sogand Goudarzi; Fatemeh Dehghani Firouzabadi; Fatemeh Moosaie (Babol University of Medical Sciences, 2020)
Background: The outbreak of coronavirus disease 2019 (COVID-19) has become a global crisis, as the World Health Organization (WHO) declared COVID-19 as a global pandemic. Complete heart block, resulting from an abnormal heart rhythm, is a rare presentation of this infection, which can be life-threatening due to possible progression into ventricular tachycardia. Case Presentation: We report a critical case of COVID-19 in a young woman without any medical history. She was admitted to the hospital with a rare, but serious presentation of temporary complete heart block with a skin rash after three weeks of treatment with an antiviral agent and hydroxychloroquine. The result of cardiac monitoring, using a Holter monitor, was normal, and her sinus rhythm returned to normal without any interventions. Conclusion: This case emphasized the importance of regular follow-ups for patients with COVID-19 and highlighted the need for attention to unusual presentations, such as brief episodes of unconsciousness and chest pain.